(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
There are a number of ecological systems in nature that are directly related to each other. The article examines the problem caused by human neglect of nature, environmental pollution, the impact of a bad atmosphere, lack of fresh water on human health